Evaluation for stroke motion of crawl swimming - Homma, M. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this research was to examine the kinematic parameters effective for the evaluation of the stroke motion during crawl stroke. The motion of the upper arm under water was analyzed using video analysis via the three-dimensional panning direct linear transformation (DLT) method with three high-speed video cameras (300 fps) from under the water. Based on the video analysis, the hand fluid force was estimated using the Schleihauf model (1979), and various kinematic parameters were calculated. The participants included 15 competitive swimmers belonging to the university swimming club. From the results, seven parameters with high correlation to the mean swimming velocity during one stroke were extracted as the factors, and multiple linear regression analysis was performed with the mean swimming velocity as the response variable and the motion parameters as the explanatory variable. The estimated mean swimming velocity, according to the obtained multiple linear regression equation, had a high coefficient of determination (r2 = 0.784), which was considered to be effective as the evaluation standard for swimmers at the same level as the participants in this study. From the standardized regression coefficients, Idc2 (Index of coordination 2) that is the overlap time during both arm in water, the mean lift force of the up-sweep phase and the mean Arm-area in one stroke under water (area of projected triangle to the vertical plane, connecting wrist-elbow-shoulder points), were important parameters in relation to the mean swimming velocity.